Handbook of mathematical economics ed. by Kenneth J. Arrow and Michael D. Intriligator.. - Intriligator, Michael D.; Arrow, Kenneth Joseph. (Handbooks in economics)
Analisi: TEORIA ECONOMICA. Opere generali. MANUALI. Teoria economica. ECONOMETRIA. Applicata. Matematica.